Pengayaan Fitur Laporan Pada Senayan Library Management System (Slims) Di Perpustakaan President University - Erus Effendi; Meuthia Rachmaniah; Irman Hermadi (Perpustakaan IPB, 2015)
Information technology application of in libraries functionsin a variety offorms, one of which shaped by the utilization of libraryi nformation system to enablet he processing of data and reports quickly. Therefore the libraryi nformation system is in dispensable in determining business decisions. The development of library information systems are needed to carried out in accordance with the need of the business process. The purposeof this research is developing feature reports SliMS at President University Libraryto meet business process. SLiMS has been chosenasone of the development library information system to creat the enrichment of the report feature. They are Annual Circulation, Circulation per Capita, Membership Report, Registration as a Percentage of Population, Visitor perYear, Library Visit perCapita, Growing of Collection, with using the method of prototyping model.The Testing sistem results the enrichment of report feature can help to create library report with user friendly dan based on decision making for future library planning at President University Library.Keywords: Management Information System, Reporting SLiMS, Prototyping, University Library.